RPL21 siRNA Blocks Proliferation in Pancreatic Cancer Cells by Inhibiting DNA Replication and Inducing G1 Arrest and Apoptosis - Li, Chaodong; Ge, Mei; Chen, Daijie; Sun, Tao; Jiang, Hua; Xie, Yueqing; Lu, Huili; Zhang, Baohong; Han, Lei; Chen, Junsheng; Zhu, Jianwei (Frontiers in Oncology, 2020)
Background: Our previous study showed that the ribosomal protein L21 (RPL21) is important for the development and survival of pancreatic cancer (PC). In this study, experiments were performed with RPL21-specific small interfering RNA (siRNA) to elucidate the mechanism by which RPL21 controls PC PANC-1 and BxPC-3 cells proliferation. Method: In the present study, PANC-1, BxPC-3 cells, and BALB/c nude mice were used to investigate antitumor effect and mechanism by which RPL21 controls cells proliferation and apoptosis in vitro and in vivo. The effects of RPL21 knockdown on PANC-1 and BxPC-3 cells proliferation, cell cycle and cell apoptosis in vitro were determined using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assays and flow cytometry assay. The mechanism of RPL21 regulating cell proliferation was investigated using transcriptome sequencing analysis and luciferase reporter assay. The effects of RPL21 knockdown on PANC-1 and BxPC-3 cells proliferation in vivo were determined using BALB/c nude mice tumor model. Results: In PANC-1 and BxPC-3 cells, the knockdown of RPL21 expression with corresponding siRNA suppressed cell proliferation in vitro and in vivo, inhibited DNA replication, and induced arrests in the G1 phase of the cell cycle. Further results showed that the mini-chromosome maintenance (MCM) protein family (MCM2-7), CCND1 and CCNE1 were down-regulated significantly in PANC-1 and BxPC-3 cells after transfected with RPL21 siRNA, which suggests that the suppression of DNA replication is due to the reduced expression of MCM2-7 family, and the induction of G1 arrest is correlated with the inhibition of CCND1 and CCNE1. Luciferase reporter assay showed that RPL21 controls the DNA replication and G1-S phase progression possibly through the regulation of E2F1 transcription factor in PC cells. Moreover, RPL21 siRNA showed an apoptosis-inducing effect only in PC PANC-1 and BxPC-3 cells but not in normal cells. The increase of caspase-8 activities and the loss of mitochondrial membrane potential after RPL21 silencing indicates that the RPL21 gene was involved in caspase-8-related mitochondrial apoptosis. Conclusion: Our findings suggest that siRNA against the RPL21 gene possesses a potential anti-cancer activity for PC cells by inhibiting their proliferation and DNA replication, as well as inducing cell cycle G1 arrest and cell apoptosis.